Flexible Viologen Cyclophanes: Odd/Even Effects on Intramolecular Interactions. Issue 7 (14th February 2017) - Berville, Mathilde; Choua, Sylvie; Gourlaouen, Christophe; Boudon, Corinne; Ruhlmann, Laurent; Bailly, Corinne; Cobo, Saioa; Saint‐Aman, Eric; Wytko, Jennifer; Weiss, Jean
Abstract: The ability of three bis‐viologen cyclophanes to act as redox‐triggered contractile switches is investigated. Odd/even effects in the formation of cyclic bis‐viologens are circumvented by the use of a Zincke salt intermediate and a tetrathiafulvalene template to prepare a flexible cyclophane with hexyl linkers. Comparative spectro‐electrochemical studies of this macrocycle with two other pentyl‐ or heptyl‐linked cyclic bis‐viologens show that the development of intramolecular interactions in aqueous solution depends on the length of the bridges. This dependence is confirmed by EPR and DFT studies of the magnetic coupling in the diradical dication species. The anti‐ferromagnetic or ferromagnetic nature of the coupling depend, respectively, on the odd or even number of methylene groups in the spacer. Abstract : Important links : Three bis‐viologen cyclophanes are investigated as redox‐triggered contractile switches. The use of a Zincke salt intermediate and a tetrathiafulvalene template allows preparation of a flexible cyclophane with hexyl linkers. The intramolecular interactions in aqueous solution depend on the length of the bridges, as determined by spectro‐electrochemical, EPR, and DFT studies.